Turkey : Sixth Review and Inflation Consultation Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria; Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
The staff report for the Sixth Review and Inflation Consultation Under the Stand-By Arrangement on Turkey explains the macroeconomic framework and monetary and exchange rate policies. High interest rates, slowing credit growth, and election-related uncertainty were expected to weigh on private domestic demand and keep growth near its estimated long-term potential of 5 percent. The central bank renewed its commitment to building international reserves for prudential reasons. There was broad agreement on the need to ease labor regulations and taxes as fiscal resources permit.